Development and Validation of CALR Mutation Testing for Clinical Diagnosis. Issue 5 (1st November 2015) - Maier, Cheryl L.; Fisher, Kevin E.; Jones, Heather H.; Hill, Charles E.; Mann, Karen P.; Zhang, Linsheng
Abstract: Objectives: To validate a diagnostic assay for detecting CALR mutations in the clinical setting. Methods: Traditional polymerase chain reaction (PCR) was performed on DNA previously extracted from 60 specimens (30 bone marrow aspirates [BMAs] and 30 peripheral blood [PB] samples) from 55 patients. Nearly all reported CALR mutations are insertions or deletions in exon 9. Therefore, we performed amplicon sizing by capillary electrophoresis and fragment length analysis (FLA) to determine mutation status. Mutations were confirmed by Sanger sequencing. Results: Fourteen samples from 10 patients with JAK2 and MPL wild-type myeloproliferative neoplasms were positive for CALR mutation. Detected mutations included a 52–base pair (bp) deletion (n = 6), a 5-bp insertion (n = 2), a 31-bp deletion (n = 1), and a 61-bp deletion (n = 1). Sanger sequencing of 15 samples showed 100% concordance. Matched patient PB and BMA samples (n = 5) harbored identical mutations, and samples run multiple times (n = 8) showed 100% reproducibility. Conclusions: We conclude that CALR mutations may be quickly and accurately detected by FLA of PCR amplicons by capillary electrophoresis. These methods are routine procedures for most molecular laboratories and should allow for straightforward incorporation of the CALR assay into the clinical diagnostic testing menu.